Social sciences and comparative research in Europe : cross-national and multi-disciplinary projects for urban development. The role of geography - Armando Montanari (Belgeo)
In the aftermath of the Second World War, UNESCO sought to build peace in the world through the exchange of knowledge. To this end, it developed a number of initiatives to encourage international cooperation among social scientists. These initiatives were of particular importance in Europe, where there was a clear divide between Eastern and Western European countries. After the fall of the Berlin Wall, comparative research came to signify the transfer of knowledge and the promotion of innovation. Over the past two decades the study of urban phenomena, alongside social and economic issues, has taken on a strategic role in reducing pollution, safeguarding the environment and improving the quality of life of inhabitants. The process of enlarging the scope and objectives of policy has also led to a change in the role played by geography, which is increasingly required to offer instruments of scientific communication between the natural and social sciences.